Development of a Novel Microwave Powered Method for Reducing Moisture and Microbes for Mitigating Public and Environmental Health Risks - Aditya Pandey; Omeed Momeni; Pramod Pandey (IEEE Journal of Microwaves)
Recycling of animal manure and its uses as a fertilizer for crop growth could meet increasing demand of nutrients including phosphorous and nitrogen. However, one of the major issues with manure application is the presence of pathogenic bacteria in manure and associated risks to food, and public health. Further, manure-borne bacteria causes greenhouse gas emissions (GHG) in the presence of moisture under anaerobic conditions, and recently a substantial emphasis is given to advance manure management for mitigating GHG emissions and associated environmental and climate effects. The application of microwave technology could play a crucial role in mitigating these risk conditions, and improve livestock waste management and its application. In this research, a novel microwave powered method for treating dairy manure was developed and a series of experiments were undertaken to understand to what extent microbes including pathogenic organisms such as E. coli and moisture in manure can be controlled to determine the adequate conditions that potentially reduce the methane emissions, and protects public and environmental health. We found that microwave based treatment technology is capable of inactivating dairy manure-borne bacteria, and moisture rapidly, which are potentially responsible for biological methane emissions and microbial risks to food, and public health. Results suggest that a limited time (< 5 min) exposure to microwave can eliminate pathogen indicator such as E. coli from manure, and reduces microbial activities and regrowth of microbes. These results indicate that the capacity of microwave to generate heat and eliminate microbes could control the unwanted bacteria and excess moisture in manure rapidly, and reduce public and environmental health risks.